Legal Protection of Child Victims of Sexual Crimes in the Perspective of Criminal Law - Sri Utami; Hepy Krisman Laia; Muhammad Arif Sahlepi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines legal protection for child victims of sexual crimes from a criminal law perspective. Using a normative approach and literature review, this study aims to determine the legal protection for child victims of sexual violence, factors that influence the occurrence of sexual violence against children, and efforts to prevent sexual violence against children. The results of this study indicate that Indonesia has a responsibility to protect child victims of crime. Law Number 23 of 2002 in conjunction with Law Number 35 of 2024 in conjunction with Law Number 17 of 2016 concerning Child Protection provides a basis for protection that includes children's rights, protection from violent crimes and discrimination, and fulfillment of their dignity and honor. Special protection is given to child victims of sexual violence through rehabilitation, protection of victim identity, guarantee of safety for victim witnesses, and accessibility to case developments. Criminal sanctions for perpetrators of sexual violence against children are regulated in the Law and the Criminal Code. In handling cases of sexual violence, the role of forensic medicine is crucial in terms of collecting the necessary evidence. The principle of diversion is also applied in handling cases of sexual violence involving minors. Serious coordination between the police, prosecutors, and judges is needed to eradicate sexual violence against children. In closing, this study presents a general overview of legal protection for child victims of sexual crimes from a criminal law perspective. Efforts continue to be made to strengthen the protection and prevention of these crimes through coordination between institutions and effective law enforcement.